Design of Remote Monitoring Application on Non-Rechargeable Battery Redundant System - Wahyudi Purnomo; Wahyu Adhie Candra; Gabriel Muhammad Manuel (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
In this era of continuously evolving technology, remote monitoring has emerged as an innovative and effective solution for monitoring and managing remote areas. Design of Remote Monitoring on Non-Rechargeable Battery Redundant System proposes an improved system for multi-point to point remote monitoring, battery redundant, and communication. The study investigated the accuracy of INA219 sensor readings on the battery, the Quality of Service (QoS) of the Message Queuing Telemetry Transport (MQTT) communication protocol from multiple devices based on the TIPHON standard, and the utilization of a High-Side Bootstrap circuit for the battery redundant system. The results indicate that the INA219 sensor shows an average error of 0.64% - 1.04% for voltage and 1.17% - 2.45% for current. Quality of Service testing revealed an average delay of 40.9 - 119.7 ms with 0% packet loss, thus meeting the excellent standard. Bootstrap High-Side circuit efficiency average from all devices are 99.35% for input and 95.9% for output. Lastly, the redundant system by utilizing Bootstrap High-Side circuit achieved a 100% success rate for all devices, confirming the successful design implementation.